DAYA TAHAN GARIS REKAT LRF PADA KAYU LAMINA MANII TERHADAP SERANGAN RAYAP KAYU KERING The LRF Glue Line Durability of Manii Laminated Wood Against Dry wood Termite - Adi Santoso; Jasni Jasni (Masyarakat Peneliti Kayu Indonesia, 2003)
Lignin is one of the principal components constituting wood bulk, besides cellulose and hemi cellulose. It consists of poly-phenolic molecules, serving as a binding agent, which holds the wood cells together. Lignin is also credited with imparting rigidity or stiffness to the wood, rendering its body effectively resistant to the mechanical forces imposed on it. Considering and evaluating the specific attributes of lignin, an idea has come-up to utilize it as a binder or glue in the manufacture of particleboard, plywood, or other wood products.The lignin in the sulphate’s black liquor (known as Kraft lignin) has a strong affinity when being reacted with formaldehyde to form lignin formaldehyde adhesives; and to increase the bonding strength quality, the lignin is further co-polymerization with resorcinol to form lignin resorcinol formaldehyde (LRF) resins. The resin can be employed in the manufacture of particular glued wood products such as finger-jointed wood assembly and glue laminated lumber (glulam). The research was aimed to determine the optimum composition of mole ratio in LRF glue and its pressing duration in laminated wood manufacture for construction qualities with high durability on against dry wood termite. The adhesive was prepared by mixing the isolated lignin, resorcinol and formaldehyde at various mole ratios L : R : F ( 1 : 0.5 : 2; 1 : 0,7 : 2; 1: 0,9 : 2 and control) respectively, and the pressing duration was employed by 3, 6, 12 and 24 hours at room temperature. The research results showed that the higher the resorcinol content, the longer pressing time, the higher the mortality and the lower weight loss. The mortality reaches 91.67 % and weight loss 2.17 %.